2014
DOI: 10.1136/bjophthalmol-2014-305860
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of M-CSF and IL-13 in vitreous of patients with proliferative diabetic retinopathy: implications for M2 macrophage-involving fibrovascular membrane formation

Abstract: These findings indicate that the M2 polarisation of macrophages is induced by M-CSF and IL-13 in diabetic retinas. The presence of M-CSF and IL-13 would then promote FVM formation by periostin production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…A previous study has shown that Th2 cells are one of the cellular components in FVMs of PDR patients 30 . We have also reported an increase of the IL-13 level in the vitreous of patients with PDR 27, 28. Based on these findings, the IL-13 produced by CD4-positive Th2 cells may be the inducer of POSTN secreted by the retinal vascular endothelial cells in ischemic retinas.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…A previous study has shown that Th2 cells are one of the cellular components in FVMs of PDR patients 30 . We have also reported an increase of the IL-13 level in the vitreous of patients with PDR 27, 28. Based on these findings, the IL-13 produced by CD4-positive Th2 cells may be the inducer of POSTN secreted by the retinal vascular endothelial cells in ischemic retinas.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, our earlier studies have shown a strong positive correlation between M2 macrophage markers and POSTN in the vitreous of PDR patients 33 . We have subsequently shown that macrophage polarization toward M2 phenotype by IL-13 resulted in the production of POSTN 28 . Thus, αSMA-positive pericytes and M2 macrophages polarized by IL-13 may also produce POSTN in ischemic retinas.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In OIR mice, M-CSF is required for pathological RNV but not for the recovery of normal vasculature [12]. In line with these findings, in the retinas of diabetic rats and in the vitreous of patients with proliferative DR, M-CSF levels are significantly higher as compared with those of control subjects [59,60]. This suggests targeting M-CSF either directly or via the specific inflammatory signaling pathway as a highly promising strategy for treating ocular neovascular diseases including ROP.…”
Section: Discussionmentioning
confidence: 83%
“…In the OIR mice, M-CSF is required for pathological RNV but not for the recovery of normal vasculature (Kubota et al, 2009). In the retinas of diabetic rats and in the vitreous of patients with proliferative DR, M-CSF levels are significantly higher compared to control subjects (Liu, Xu, Jiang, & Da, 2009;Yoshida et al, 2015). This suggests targeting M-CSF either directly or via the specific inflammatory signaling pathway as a highly promising strategy for treating ocular neovascular diseases including ROP.…”
Section: Retinopathymentioning
confidence: 99%